#1

+26258

0

Same process as for https://web2.0calc.com/questions/the-quadratic-x-2-20x-36-can-be-written-in-the-form, except you now compare the coefficient of the x^2 term as well.

a(x - h)^2 + k → a(x^2 - 2hx + h^2) + k → ax^2 - 2ahx + ah^2 +k

coeff of x^2: a = 3

coeff of x: -2ah = -6

constant; ah^2 + k = -2

I'll leave you to complete it!

Alan 12 mins ago

edited by Alan 9 mins ago

#2

0

So the answer would be -7?

edit

Guest 6 mins ago

#3

0

no -7 didn't work can you tell me how to complete it please?

edit

Guest 0 mins ago

AnonymousConfusedGuy
Oct 22, 2017